2004
DOI: 10.1111/j.1440-1746.2004.03474.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic gastric mucosa in the cervical esophagus (inlet patch): Endoscopic prevalence, histological and clinical characteristics

Abstract: Heterotopic gastric mucosal patches in the proximal esophagus should not be overlooked during endoscopy because they may lead to important complications in relation to their acid secretion, which may vary according to their parietal cell mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
1
18

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 28 publications
7
82
1
18
Order By: Relevance
“…Microscopically, the patch can be lined with fundic or gastric body type glands (1)(2)(3). The prevalence of EGM ranges www.bjournal.com.br from 0.1 to 4.9% in most series, reaching 10% in a prospective study (1)(2)(3). The presence of Helicobacter pylori has been reported in 20 to 56.5% of cases (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microscopically, the patch can be lined with fundic or gastric body type glands (1)(2)(3). The prevalence of EGM ranges www.bjournal.com.br from 0.1 to 4.9% in most series, reaching 10% in a prospective study (1)(2)(3). The presence of Helicobacter pylori has been reported in 20 to 56.5% of cases (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…It presents as either a single or multiple patches localized just below the upper esophageal sphincter. Microscopically, the patch can be lined with fundic or gastric body type glands (1)(2)(3). The prevalence of EGM ranges www.bjournal.com.br from 0.1 to 4.9% in most series, reaching 10% in a prospective study (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…One study that had looked specifically at patients with laryngopharyngeal reflux found significantly more HGMP/CIP in patients than controls, those without LPR symptoms (11.4% vs. 1.6%, p<0.05). These patients also had significantly more laryngeal acid reflux documented on pH study (Akbayir N. et al, 2004). Similarly, other studies have found more laryngopharyngeal reflux symptoms in patients with HGMP/CIP (Akbayir et al, 2004;Baudet et al, 2006;Borhan-Manesh & Franum, 1993;Tang et al, 2004).…”
Section: Clinical Manifestationsmentioning
confidence: 62%
“…In contrast, MUC5AC positivity was noted on the surface, pits and the glands of Barrett's esophagus. The HGMP/CIP can also be colonized by Helicobacter pylori and the patches are subjected to changes that are seen in the stomach (Akbayir et al, 2004;Alagozlu et al, 2010;BorhanManesh & Franum, 1991Gutierrez et al, 2003;Jacobs et al, 1997;Maconi et al, 2000;Poyrazoglu et al, 2009;Tang et al, 2004;Yüksel et al, 2008). Chronic inflammatory changes can be seen and progression to atrophy, intestinal metaplasia, dysplasia and malignant transformation have been reported (Borhan-Manesh & Franum, 1991).…”
Section: Histologymentioning
confidence: 99%
“…The second condition is heterotopic gastric mucosa (HGM) more frequently associated with the cervical esophagus (3). Its appearance varies from tiny microscopic foci to large areas of red or salmon-red mucosa.…”
Section: Introductionmentioning
confidence: 99%